(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
Field experiments were conducted during 2017 and 2018 rainy seasons at the Kogi State Agricultural Development farm at Karara (Lat. 8.230N, Long. 6.560E Alt. 343.00m) in Kogi State, Nigeria to investigates the influence of different cropping patterns and crop nutrient sources on yields of Soybean-Maize intercrops. Treatment consisted of two crops (Maize and Soybean), two fertilizer sources [Organic source (Poultry Manure) and Mineral Fertilizer (Urea)] and Intercropping patterns (2:2, 2:3, 2:4, 2:5), sole maize and soybean as control. All the treatments were given factorial combination and laid in a Randomized Complete Block Design (RCBD) and replicated three times. The experiment was carried out for two years, the averages obtained indicates the superiority of 2:2 intercropping system over all other systems as exemplified by higher Land Equivalent Ratio (LER) of 1.13, Aggressivity (A) of 0.458, and Competitive Ratio (CR) of 1.63. The 2:2 intercropping system however showed the lowest Relative Crowding Coefficient (RCC) of 0.088 which is an indication for high productivity. Application of mineral fertilizer in the form of Urea was found to be more effective than the use of Poultry manure in both years of the experiment soybean had higher Relative Crowding Coefficient (RCC), Competitive Ratio (CR), and Aggressivity (A) values than maize. Use of mineral fertilizer in the form of urea was more effective than poultry manure in both years. Soybean was more superior in competition than maize, and its productivity dominated the total biomass yields. It was therefore concluded that intercropping soybean with maize at a 2:2 ratio has the potential to improve not only the seed yield but other associated biological yields and high land use efficiently.